ANALISIS PROGRAM INKLUSI DI SD PLUS DARUL ULUM JOMBANG PERSPEKTIF KONSTRUKTIVISME VYGOTSKY - Musbichin Musbichin; Nurul hidayah; Hilyah Ashoumi (Jurnal Manajemen Pendidikan, 2026)
Objective: This study aims to analyze the implementation of the inclusive education program at SD Plus Darul Ulum Jombang through Lev Vygotsky’s social constructivist perspective to understand how inclusive learning practices support the academic and social development of students with special needs. Method: This study employed a qualitative approach with a descriptive-analytical design. Data were collected through classroom observations, in-depth interviews with teachers and school stakeholders, and document analysis. The data were analyzed interactively through data reduction, data display, and conclusion drawing. Results: The findings indicate that inclusive education has been implemented by integrating students with special needs into regular classrooms with appropriate instructional adjustments. Teachers applied differentiated instruction, gradual task assignments, and collaborative learning strategies that enhanced students’ participation, social interaction, and learning independence. However, the implementation still faces challenges, particularly regarding the limited number and competence of special assistant teachers and the varying levels of understanding among teachers and parents concerning inclusive education. Novelty: This study highlights the relevance of the Zone of Proximal Development (ZPD) and scaffolding concepts in explaining the effectiveness of inclusive educational practices in elementary schools. It also reinforces the application of Vygotsky’s social constructivist theory.